Semi Smooth Graceful Labeling on Some Graphs - V. J. Kaneria; Meera Meghpara (International Journal of Mathematics And its Applications, 2015)
This paper contains some results on semi smooth graceful graph. We proved that B_m,n, S^'(B_m,n) and S^'(P_n) are semi smooth graceful and a graph obtained by joining G and B^2_m,n with an arbitrary path P_r is a graceful.